Respuesta :

Answer:

Step-by-step explanation:

Given expression is,

[tex]\text{cot}A=\frac{1}{2}(\text{cot}\frac{A}{2}-\text{tan}\frac{A}{2})[/tex]

To prove this identity we will take the right side of the identity,

[tex]\frac{1}{2}(\text{cot}\frac{A}{2}-\text{tan}\frac{A}{2})=\frac{1}{2}(\frac{1}{\text{tan}\frac{A}{2}}-tan\frac{A}{2})[/tex]

                         [tex]=\frac{1}{2}(\frac{1-\text{tan}^2\frac{A}{2}}{tan\frac{A}{2}})[/tex]

                         [tex]=\frac{1}{2}[\frac{2(1-\text{tan}^2\frac{A}{2})}{2tan\frac{A}{2}}][/tex]

                         [tex]=\frac{1}{2}(\frac{2}{\text{tan}A} )[/tex] [Since [tex]\text{tan}A=\frac{2\text{tan}\frac{A}{2}}{1-\text{tan}^2\frac{A}{2}}[/tex]]

                         = cot A

Hence right side of the equation is equal to the left side of the equation.